Soil water content at the catchment level and plant water status relationships in a Mediterranean Quercus ilex forest - Bellot, J; Ortiz de Urbina, J M (Journal of Hydrology, 2008)
This paper presents an analysis of the forest hydrology and plant water status interaction, focusing on the relationship between the hydrological water balance at the catchment level and the predawn leaf water potential of the species Quercus ilex (holm oak). The catchment water balance approach was applied to a Mediterranean watershed forested with holm oak to evaluate the daily soil water reserve at the catchment level. After this, evapotranspiration and soil water content were combined to estimate the potential soil water reserve and evaluate plant water status at the catchment level. A close relationship was detected between leaf water potential and the soil water reserve, and was ﬁtted to a negative exponential curve to estimate predawn leaf water potential from a hydrological database. The proposed equation can help to predict the frequency, intensity, and length of droughts potentially capable of causing structural damage to the forest, from the hydrological time series records.
Keywords: Catchments; Plant water status; Predawn water potential; Quercus ilex; soil water; water balance

Una nueva técnica viverística para la introducción de plantones de DE QUERCUS SPP. EN CLIMA SECO Y SEMIÁRIDO - Vilagrosa, A; SEVA, J P; Valdecantos, a; HERNÁNDEZ, N; CORTINA, J; Bellot, J; Vallejo, V R (II Congreso Forestal Español, 1997)
We present a new technique to improve the establishment of Quercus spp. seedlings in dry and semiarid environments. It is based on the use of pre-germinated acorns transplanted in biodegradable nursery container which are transferred to the field befo re root pruning and upward root growth occurs. In this experiment we also tested the use of tree-shelters.
Keywords: bellotas pregerminadas (voyant); clima mediterráneo; plantones; Quercus spp.; supervivencia

Structure, biomass and production of a resprouted holm-oak (Quercus ilex L.) forest in NE Spain - LLEDO, M J; Sánchez, J R; Bellot, J; Boronat, J (Plant Ecology, 1992)
When considered as a compartment of nutrients (biomass) and as a flux between compartments (pro- duction) vegetation plays an important role in the biogeochemical forest research that is carried out at the Prades research station in two adjacent catchments: L'Avic (51.6 ha) and La Teula (38.5 ha). The forest density at the Prades site, considering both the tree and shrub layers, is 9182 stems ha t, with 4527 stems ha i being the tree layer. The predominant species is Quercus ilex with Arbutus unedo and Phillyrea media less common. The structure of the population, estimated by grouping the numbers of the stems in classes of 2.5 cm, shows a distribution which conforms, in both catchments, to a negative exponential equation following the Yoda law. The distribution observed at different altitudes shows great heterogeneity, the number of stems of Q. ilex increases with altitude, from 4000 stems ha ~ at 800 m, to 14000 stems ha 1 at 1000 m of altitude. The upper and the lower parts of the watershed show dif- ferences in forest production that explain this variation. In this paper the influence of human activities and physical factors on the origin of this structure is discussed. The tree and shrub biomass was cal- culated by applying allometric regressions for the three predominant species and has been estimated as 113.2 t ha 1. The tree layer accounts for 92°o. Net production was calculated from annual increases (by differences between the 1981 and 1986 basal area measures) of the woody part and the litterfall. The above-ground net production was about 6.5 t ha 1 year 1, 95.4o0 of it being from trees and shrubs and only 4.6°0 from grasses.
Keywords: Forest structure; human activities; mediterranean forest; prades; Species distribution

Chemical characteristics and temporal variations of nutrients in throughfall and stemflow of three species in Mediterranean holm oak forest - Bellot, J; Escarre, A (Forest Ecology and Management, 1991)
In this study on chemistry of throughfall and stemflow of three dominant species in a Spanish holm oak forest few significant differences were detected in the ion concentrations between Quercus ilex, Arbutus unedo and Phillyrea media. Comparison of annual average concentration of throughfall, stemflow and bulk deposition indicated nitrate and hydrogen uptake by the plants. At the same time, the data show the importance of precipitation as a source of nutrients.
Keywords: bulk deposition; Holm oak forest; nutrients (PG); stemflow; throughfall